Geneologi Suku Laut Bangka Belitung - Janawi, Janawi (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2018)
Sea nomad or sea dweller is the ethnicity embriotic of the population of nusantara. As empiric study, the migration of sea nomads happened on some centerius ago which migrate to the whole of nusantara. This tribe was labelled with deffrent terms, e.g illanun or irranun (in Serawak, Malay, Kalimantan, Filipinna and Belitung), Bajo (Sulawesi), boat people (Riau Archipelego), and Sekak or Sawang (Bangka Belitung). Beside that, in the direct way the study of sea nomads explain about the soul of Bhinneka Tunggal Ika, tribal geneology, The contruction of the nusantara history, the source of history study, and the tradition of maritim.